(untitled) (Global Journal of Human-Social Science, 2021)
The adoption of digital identification is one of the key drivers of the ongoing conversations about the multiple digitisations of the Nigerian public administration Despite the operations of identification policy in Nigeria for more than a decade the e-identification ecosystem which is expected to drive financial and social inclusion as well as enhance e-governability is being confronted with the vicious cycle of low enrollment especially among the lower class communities For instance during Covid-19 intervention the database of the indigents was revealed to be only 2 5 million in the face of extreme poverty in the country Yet subsequent governments emphasised the need for citizens onboarding on the national database citing the significant role digital identification plays in providing effective administration of public services The investigation of the post-adoption effects of the identification policy on activities of public administration agencies in Nigeria shows a dim outlook The results questioned the possibility of the ongoing digitization to effectively support the provision of governmental services to public